Relevance of the Performance of the Dipo Rite among the People of Yilo and Lower Manya Krobo in The Eastern Region of Ghana - Sewu, Narh David (South Asian Journal of Social Sciences and Humanities, 2023)
The Dipo rite is a traditional practice that has been deeply rooted in the culture of the people  of Yilo and Lower Manya Krobo in the Eastern Region of Ghana for many years. It is a rite of  passage that marks the transition of young girls into womanhood, and it is believed to be a  crucial part of the social and cultural fabric of the community. This paper provides a  comprehensive review of the relevance of the Dipo rite among the people of Yilo and Lower  Manya Krobo. The review is based on empirical and conceptual studies that explore the social,  cultural, and economic aspects of the rite. The studies reveal that the Dipo rite is an important  cultural practice that promotes social cohesion and fosters a sense of community among the  people. It is also associated with traditional beliefs and values that are deeply rooted in the  community's history and identity. The studies further show that the Dipo rite is an economic  activity that generates income for the community, particularly for those who provide services  and products associated with the rite. Finally, the paper proposes that the Dipo rite's relevance  can be explained through the lens of cultural ecology, which considers the relationships  between humans and their environment and how cultural practices are shaped by ecological  factors. In conclusion, this paper provides valuable insights into the relevance of the Dipo rite  among the people of Yilo and Lower Manya Krobo in the Eastern Region of Ghana and  highlights the importance of preserving this cultural practice for future generations.
Keywords: Dipo rite; Relevance; Cultural practices; Performance; Yilo; Manya Krobo